Digital library of scientific forums organized by the Faculty of Mathematics and Informatics of the University "St. Cyril and St. Methodius "- Veliko Tarnovo - Georgieva Trifonova, Tsvetanka; Zdravkov, Kaloyan (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
The increasing needs to expand access to research results and insufficient opportunities for publication in printed issues put a serious challenge to the scientific community. The aim of the paper is to mark the first step towards solving this problem in the Faculty of Mathematics and Informatics of the Veliko Tarnovo University by building a repository of digital documents using open source software.